Studi Literatur Aktivitas Antibakteri Ekstrak Daun, Kulit Buah, Biji Kopi Arabika (Coffea arabica) dan Robusta (Coffea canephora) Terhadap Berbagai Bakteri - Febriani, Amelia; Koriah, Siti; Syafriana, Vilya (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2023)
Coffee is a plant containing secondary metabolite compounds with potent antibacterial activity in its leaves, seeds, and even fruit peel. This study aims to analyze the antibacterial activity of extracts from arabica (Coffea arabica) and robusta (Coffea canephora) coffee leaves, fruit peel, and seeds against various bacterial strains. The research was conducted using a literature review method, employing databases such as Pubmed, Google Scholar, and Science Direct, and utilizing a combination of different keywords such as antibacterial, arabica coffee leaves, robusta coffee leaves, arabica coffee fruit peel, robusta coffee fruit peel, arabica coffee seeds, robusta coffee seeds, diffusion, and dilution. According to the findings of various studies, the coffee plant contains alkaloids, flavonoids, tannins, steroids, saponins, phenols, caffeine, and chlorogenic acid. Extracts of leaves, fruit peels, arabica coffee beans, and robusta coffee beans were obtained using maceration and heating extraction procedures such as soxhletation and steeping. These extracts were found to be effective at inhibiting the growth of Staphylococcus aureus, Escherichia coli, Edwardsiella tarda, and Streptococcus agalactiae. Robusta coffee leaf extract has the ability to suppress the growth of microorganisms such as Staphylococcus aureus, Escherichia coli, Bacillus subtilis, and Klebsiella pneumoniae. Arabica and robusta coffee fruit peel extracts have been shown to suppress the growth of bacteria such as Staphylococcus aureus, Vibrio cholerae, and Escherichia coli. Arabica coffee bean extract has been shown to prevent the growth of Lactobacillus acidophilus and Enterococcus faecalis, whilst robusta coffee bean extract has been shown to inhibit the growth of Staphylococcus epidermidis, Staphylococcus aureus, and Escherichia coli.